Can myocardial remodeling be a useful surrogate predictor of myocardial iron load? A 3D echocardiographic multicentric study. Issue 10 (6th June 2018) - Agha, Hala Mounir; AbdelMassih, Antoine Fakhry; AbdelRahman, Mohamed Youssef; Milanesi, Ornella; Castaldi, Biagio; Geranio, Giulia; Putti, Maria Caterina; Kharabish, Ahmed; Esmail, Reem; El‐Kamah, Ghada; Hamdy, Mona; El‐Baz, Heba; et al.
Abstract: The relationship between myocardial iron load and eccentric myocardial remodeling remains an under‐investigated area; it was thought that remodeling is rather linked to fibrosis. This study aims to determine whether or not measures of remodeling can be used as predictors of myocardial iron. For this purpose, 60 patients with thalassemia were studied with 3D echocardiography and myocardial relaxometry (T2*) by Cardiac MRI. 3D derived sphericity index was significantly higher in patients with myocardial iron load. It was correlated with T2* with a 100% sensitivity and specificity (cut‐off value of 0.34) to discriminate between patients with and without myocardial iron overload.